PERNIKAHAN LINTAS AGAMA DALAM BAYANG-BAYANG AMBIGUITAS HUKUM: TINJAUAN TERHADAP UU NO. 1/1974 DAN PUTUSAN MA–MK - Dyatmika, Gede Dewangga Prahasta; Dewi, Cokorde Istri Dian Laksmi; Dewi, Kadek Ary Purnama (RIO LAW JURNAL, 2025)
Interfaith marriage in Indonesia is a complex legal issue that remains unresolved within the national legal framework. Law No. 1 of 1974 on Marriage does not explicitly address interfaith marriage, leading to various conflicting legal interpretations. Rulings by the Supreme Court and Constitutional Court in relevant cases have reinforced ambiguity and contributed to legal uncertainty. This study aims to examine the legal vacuum surrounding interfaith marriage regulation and analyze the juridical implications of disharmony between statutory law and court decisions. Using a normative juridical approach, the research reviews legislation, jurisprudence, and legal doctrines. Findings indicate that the absence of clear provisions creates legal gaps that disadvantage citizens in exercising their constitutional right to marry. Therefore, a reformulation and harmonization of the law is urgently needed to reflect Indonesia's religious diversity and social realities, and to ensure the protection of human rights and legal certainty for interfaith couples.Keywords: interfaith marriage; legal vacuum; ambiguity; Marriage Law; MA–MK rulings